Advances in the Study of Pancreatic Exocrine Diabetes Mellitus - Wang, Sijing; Duan, Yuhong (Journal of Contemporary Medical Practice, 2025)
Pancreatogenic diabetes, also known as type 3c diabetes mellitus, is a distinct form of diabetes caused by disorders of the exocrine pancreas. In recent years, significant advances have been made in understanding its pathogenesis, diagnosis, and therapeutic strategies. However, clinical diagnosis remains challenging, as the condition is often misdiagnosed as type 2 diabetes mellitus, leading to inappropriate treatment and poor prognosis. Currently, diagnosis relies on clinical history, imaging studies, and evaluation of pancreatic exocrine function. Compared with the more prevalent type 2 diabetes, patients with pancreatogenic diabetes face greater difficulty in glycemic control, more frequent episodes of hypoglycemia, higher insulin requirements, and more complex treatment regimens. Management requires a comprehensive approach to address both exocrine insufficiency and hyperglycemia. Pancreatic enzyme replacement therapy can improve nutrient absorption, while insulin and oral hypoglycemic agents remain the mainstays of glucose control.